Pembentukan Karakter Murid (Studi terhadap Sekolah Dasar Islam Terpadu Al-Fityah Pekanbaru) - Yunita, Yenni (UIR Press, 2018)
Character education is essentially required to be applied in educational institutions and in the teaching system of education today. Without character education, it means permitting the mix of clarity of understanding of moral values ​​and ambiguous nature which prevent students from making decisions based on a strong moral foundation. This study is a field research which aims to determine the formation of character and factors that influence the formation of character of students at the Al-Fityah Integrated Islamic Primary School Pekanbaru. The type of research is qualitative research. The subject of this study was teachers at the Alfityah Pekanbaru Integrated Islamic Primary School, amounting to 42 people. While the objects in this study were Al-Fityah Islamic Primary School Students totaling 439 people. Data collection techniques in research are observation, interviews, and documentation. Based on the results of this study, it showed that the Formation of students' Characters in the Al-Fityah Integrated Islamic Primary Schools Pekanbaru essentially teaches andimplements Islamic manners to students and then refuses them in their daily lives both in the school environment and in the home environment with reference to 10 muwasafat. Character formation is good in the school environment and it directly guided and cared for by the teachers, while at home the character formation of the children is guided by both parents through the Adab Monitoring Book (BMA) and then evaluated by the teacher at school. There are several factors that influence character formation, namely: family or parents, friends, environment, and the influence of television and other electronic media including the internet.